Financing the German Mittelstand - Audretsch,David; Elston,Julie (Small Business Economics, 1997)
This paper describes how the German Mittelstand, or small- and medium-sized enterprises, are financed in Germany. The role of the German Mittelstand, both in a static and in a dynamic framework, is described and contrasted with that of the same size group in other leading industrialised countries. We find that in general, the Mittelstand has played a mmore important role in Germany than in other industrialised nations, such as the United States or the United Kingdom. The traditional success of the German Mittelstand is partly attributable to a system of finance that is richly layered by complementary institutions designed to meet the financial needs of both large and smaller enterprises. However, we find evidence that even under the German system of finance liquidity constraints exist and are greater for smaller firms. The German system of finance moreover seems particularly deficient in the channeling of funds to new firm startups in the newer industries.
Keywords: Finance; OSU-Cascades